Gender disparity in nutritional status among under five children in Rajshahi city, Bangladesh - Yeasmin, K; Islam, KMS; Yeasmin, T (Journal of Bio-Science, 2019)
Girls face discrimination from the moment of her birth. Different underlying factors are responsible for this disparity. Though in recent decades, there is a significant advance in gender disparity, it is still prevalent in different aspect of life throughout the world. Yet a wide level of disparity still exists, whether implicit or explicit, in nutrition and child cares both in the rural and urban areas. Thus, the aim of the study was to determine the gender disparity in nutritional status among under five children in Rajshahi City, Bangladesh. A community based multi-stage cross-sectional study were accomplished for collecting anthropometric and household socio-demographic data of under-five (36≤ age ≤59) children to assess gender disparity on nutritional status in Rajshahi City, Bangladesh. It was performed during the period March 2017 to September 2017. Simple random sampling was used to select children from households by applying multistage sampling technique. Data were analyzed using WHO anthro 2005 software (WHO, Geneva, Switzerland) and Statistical Package for Social Sciences IBM (SPSS) version 22.0. A value of p<0.05 was regarded as statistically significant in the analysis. Under five 371 girls with mean age 47.26 ± 8.33 months and 366 boys with mean age 48.28 ± 7.75 months were participated in this study. No failure in composite anthropometry/normal healthy boys and girls were found 46% and 36% respectively. The prevalence of moderate underweight, stunting and wasting among girls were 23.5%, 27.5% and 14.6% respectively, whereas, among boys 22.7%, 25.4% and 9.8% respectively. Deficiency of energy intake, insufficiency of macro and micro nutrients increase the chance of suffering protein-energy malnutrition, nutritional disorders among girls, compared to boys. Aggregating social development and intervention program of Government may help to reduce gender disparity and improve the nutritional status of overall all children. J. bio-sci. 27: 1-10, 2019